Construction of chimeric antibody binding green fluorescent protein for clinical application - Isarankura-Na-Ayudhya, Chartchalerm; Prachayasittikul, Virapong; Suwanwong, Yaneenart; Tantimavanich, Srisurang (Technische Universität Dortmund, 2005)
A chimeric antibody-binding green fluorescent protein (ZZGFPuv) was successfully constructed and applied as a powerful tool for immunological diagnosis. A gene encoding two repetitive sequences of Z-domain, derivative of IgG-binding B domain of staphylococcal protein A, was fused in-frame to the N-terminus of gfpuv gene. The chimeric gene was subsequently transformed and expressed in various strains of E. coli. Expression of chimeric protein in E. coli strain HB101 resulted in a protein translocation from cytoplasm to periplasmic space and cultivation medium. The chimeric ZZGFPuv could be purified using either IgG Sepharose column or immobilized metal (Cu2+) affinity chromatography. The purified protein migrated in non-denaturing SDS-PAGE as two major bands. A fluorescent band was located at 36 kDa while another band at 48 kDa exhibited non-fluorescence. The fluorescent band was isolated and assessed for IgG-binding via fluorescent emission. The lowest amount of IgG that could be detected by dot immunobinding assay was approximately 630 ng. Indirect immunofluorescent assay for a serological detection of leptospirosis was performed by using the chimeric ZZGFPuv as IgG detector. A strong fluorescent intensity as comparable to that of the fluorescein isothiocyanate (FITC) conjugated system was significantly detected. All these findings support a high feasibility to apply the chimeric Ab-binding GFP for clinical applications in the future.
EXCLI Journal ; Vol. 4, 2005
Keywords: Fc binding; green fluorescent protein; Z-domain; 610